2021
DOI: 10.3390/ijerph18073825
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Profile in Female Cyclists and Its Relationship with Age, Training Parameters, Sport Performance, and Injury Incidence

Abstract: Previous studies have highlighted the importance of psychology on sports performance and its relationship with the incidence of sport injuries. The objectives of the present investigation were: (1) to analyze the psychological profile of female cyclists as a function of age, training parameters, sport performance, and injuries suffered and (2) to design a model to predict their psychological profile. Sixty-one female cyclists participated in the study. Differences were found as a function of a competitive cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Regarding motivation, the results are contrary to those of previous studies conducted on soccer players in which no differences in motivation were found between the different playing positions [ 37 ]. This could be due to the fact that the present research was conducted with elite female players, while the previous research was conducted on amateur players [ 37 ], since the performance obtained during training and matches is highly related to the extrinsic motivation of the players [ 38 ]. Thus, elite players show a higher performance than amateurs in shooting and passing ability, as well as in the ability to sprint [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding motivation, the results are contrary to those of previous studies conducted on soccer players in which no differences in motivation were found between the different playing positions [ 37 ]. This could be due to the fact that the present research was conducted with elite female players, while the previous research was conducted on amateur players [ 37 ], since the performance obtained during training and matches is highly related to the extrinsic motivation of the players [ 38 ]. Thus, elite players show a higher performance than amateurs in shooting and passing ability, as well as in the ability to sprint [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another important reason for the sex difference in participation might be psychological motives. Exercise is often used to compensate for stress, as a coping mechanism, to find inner peace, and to build self-esteem [ 48 ]. Due to existing sex differences in psychological variables, such as competitive anxiety, emotional stability, or emotion control [ 48 ], it is important to include psychological motives, which may lead to the assumption that women tend to choose the less challenging races for different motivational reasons.…”
Section: Discussionmentioning
confidence: 99%